(3dHGH GdefGSc hYHGH GdeSGdcs - (3GdQTjOj , YHO Gddg GdSfOjhfj,J (B1265 (3g` s ((3Ydi GdYHGOi s)
(3ChdgG (B:s
(3hHYO agPG dHGH GdefGSc hYHGH GdeSGdc s
(3BNQgG (B:s
(3GdeWdhH hGdeSFhd hfgGjI GdebUhO hGdeCehd s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B25s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B400s
Keywords: (3CUhd Gdabgs